Novel functions of FoxM1: from molecular mechanisms to cancer therapy - Alvarez-Fernández, Mónica; Medema, René H. (Frontiers in Oncology, 2013)
FoxM1 is a member of the forkhead family of transcription factors. Since its identification 15 year ago, numerous studies have progressively contributed to our current understanding on FoxM1 functions. Early work showed that FoxM1 regulates the transcriptional program of the G2 phase of the cell cycle, and is essential for proper mitotic progression and genomic stability. Moreover, FoxM1 was found to be overexpressed in many different types of human cancer, suggesting a role of FoxM1 in tumor proliferation. In the past years, a significant number of studies have formally demonstrated the involvement of FoxM1 in different aspects of tumorogenesis, including angiogenesis, invasion, and metastasis. In addition to this, recent studies have placed FoxM1 in DNA damage response and senescence pathways, two pathways relevant to tumor progression and the response to cancer therapies. Here, we review and discuss the molecular mechanisms through which FoxM1 executes these new roles, and the implications for the potential use of FoxM1 as a therapeutic target in cancer.